ROLE OF SPHENOPALATINE GANGLION BLOCK IN REDUCING PERIOPERATIVE OPIOID CONSUMPTION IN TONGUE CANCER SURGERY: A CLINICAL CASE SERIES - GAUTAM, ARCHANA; BHARTI, VANDNA (International Journal of Current Pharmaceutical Research, 2026)
Objective: To determine the time interval for first rescue analgesia that is intravenous diclofenac in the post-anaesthesia care unit and assess its impact on perioperative fentanyl consumption. Methods: This case series evaluated sphenopalatine ganglion block (SPGB) as an adjunct to general anaesthesia in seven patients with carcinoma of the tongue who underwent elective surgery. The ultrasound-guided SPGB via suprazygomatic approach using 4 ml of 0.5% bupivacaine was performed after administering general anaesthesia to the patient. Results: SPGB was successfully performed within 5–6 min and was associated with 200–260ug perioperative fentanyl and 2.0–3.1µg/kg/min nitro-glycerine use. Hemodynamic remained stable, blood loss was 140–180 ml, and the surgical field improved. Postoperatively, pain scores (VAS<3) were maintained for 22–24 h, with delayed need for rescue analgesia, effectively managed with intravenous diclofenac. No major complications were observed. Conclusion: These findings suggest that SPGB is a simple, safe, and effective component of enhanced recovery after surgery (ERAS) in oral cancer surgery, reducing opioid consumption and improving surgical and postoperative outcomes.